2016
DOI: 10.1002/jcp.25283
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment of Medullary and Papillary Human Thyroid Cancer: Biological Effects of Hyaluronic Acid Hydrogel Loaded With Quercetin Alone or in Combination to an Inhibitor of Aurora Kinase

Abstract: The aim of this paper is based on the use of a hyaluronic acid hydrogel of Quercetin tested alone and in combination to an inhibitor of Aurora Kinase type A and B (SNS-314) on human medullary and papillary thyroid cancer cells. Biological investigations were focused on the cellular uptake of the hydrogel, cell viability, antioxidant, and cytokines secretion studies. Quercetin delivered from hydrogel show a time and CD44 dependent interaction with both cell lines with significant anti-inflammatory effects. Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…As previously demonstrated by our research group (Quagliariello, Armenia, et al, 2016) , temozolomide, and temozolomide associated to hyaluronic acid nanohydrogel of quercetin at 0.5 mg/ml (from 1 up to 200 μM or from 1 up to 1,000 μM of drug for A172 and T98MG cells, respectively). Sensitivity (c) of A172 and T98MG cells treated with 5-Aza-2′-deoxycitine to alkylating agent temozolomide.…”
Section: Uptake Quantification and Mechanistic Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…As previously demonstrated by our research group (Quagliariello, Armenia, et al, 2016) , temozolomide, and temozolomide associated to hyaluronic acid nanohydrogel of quercetin at 0.5 mg/ml (from 1 up to 200 μM or from 1 up to 1,000 μM of drug for A172 and T98MG cells, respectively). Sensitivity (c) of A172 and T98MG cells treated with 5-Aza-2′-deoxycitine to alkylating agent temozolomide.…”
Section: Uptake Quantification and Mechanistic Studiessupporting
confidence: 72%
“…Synthetized HA nanohydrogel (HA hydro) and HA nanohydrogel of quercetin (HA‐hydroQ) show an average hydrodynamic size of 188.5 ± 2.3 and 197.3 ± 3.3 nm, respectively with a poly dispersity index (PI) of 0.11 ± 0.018 and 0.08 ± 0.015 and a zeta potential of −31.5 ± 1.2 mV and −31.3 ± 1.1 mV (Table ). Using HPLC method, as reported in our previous studies (Quagliariello, Iaffaioli, et al, ), we calculated the loading of 0.4 mmol of quercetin/gram of hydrogel (corresponding to 40 μM of quercetin in 1 mg/ml of HA‐hydroQ solution). Furthermore FA‐HA hydroQ showed an average hydrodynamic size similar to the non‐fluorescent nanohydrogel with a mean value of 209.2 ± 3.8 nm with a low PI and always a negative zeta potential (−32 mV), (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New multi-TKIs (pyrazolopyrimidines and derivatives of CLM3) and other therapeutic classes such as inhibitors of aurora kinases, proteasome, kinesin spindle protein, cancer stem cells and histone deacetylases, flavonoids, gene and apoptotic cell death-based therapies have already shown promising results in preclinical studies, and may have a role in advanced TC therapy in the future [26][27][58][59][60][64][65][66][67][68][69][70][71]. No writing assistance was utilized in the production of this manuscript.…”
Section: Other Investigational Therapiesmentioning
confidence: 99%
“…The authors have found that quercetin had an anti-inflammatory action and also that the compounds had a synergic cytotoxic effect, thus suggesting the anti-tumor activity of the substances [115]. …”
Section: Effect Of Flavonoids On Iodide Uptake and Thyroid Cancermentioning
confidence: 99%